Microbiological Quality Analysis of Refill Drinking Water Depots in Padang City - Rahayu, Lisa; Handayuni, Linda; Barlian, Eri; Yuniarti, Elsa (CV. CENDIKIA JENIUS INDONESIA, 2024)
Drinking water is water that meets health standards and can be consumed directly. The demand for drinking water is increasing, but the challenge of water pollution is reducing the availability of clean water sources. Refill water depots have become an alternative, but their quality needs to be maintained to ensure public safety. The aim of this study is to analyze the microbiological quality of refill drinking water in Padang City. This research used a descriptive cross-sectional method with the CFU method for analyzing Total Coliform and E. coli. The results show that the majority of refill drinking water in Padang City does not meet the quality standards (0 CFU/100 ml). Out of 12 depots tested, 41.67 % depots significantly exceeded the standards, with Total Coliform reaching and E. coli > 0 CFU/100 ml. The conclusion of this study is that most refill drinking water depots in Padang City do not meet quality standards and contain E. coli and Total Coliform. It is recommended that refill water depots improve cleanliness, sanitation, equipment maintenance, and conduct routine testing to ensure water quality meets the standards. The government should strengthen monitoring and conduct periodic evaluations.